Assessment of groundwater suitability for drinking and irrigation purpose using statistical and geospatial techniques: a review - Aishverya Agrawal; Devendra Dohare (The Holistic Approach to Environment, 2023)
Water is a vital source for all living individuals on earth. The consumption of fresh water has increased rapidly in recent years. Industrialization, urbanization, and population growth have resulted in deterioration of surface and groundwater quality. It is very important to manage groundwater resources and protect them from anthropogenic activities in order to sustain life on earth. This paper discusses methods for assessing the quality of groundwater using statistical and geospatial techniques. In addition, geographic information system (GIS)-integrated statistical methods are also discussed. Statistical methods, including quality indices, irrigation water quality parameter, and geospatial methods, including inverse distance weighted (IDW) and kriging strategies for evaluating groundwater quality and assessing aquifer susceptibility are also explained. In addition, the paper provides an overview of key groundwater quality indices (GWQI) and irrigation water quality indices (IWQI) that have developed over time and used for groundwater quality evaluation around the world. It is revealed that the use of GIS-integrated advanced statistical approaches is not common in assessments of groundwater quality. The constraints and research gaps of previous studies, as well as the prospects for future research needs have been examined.